Vulnerability of Louisiana’s coastal wetlands to present-day rates of relative sea-level rise - Krista L. Jankowski (Nature Portfolio, 2017)
Coastal Louisiana wetlands face some of the world’s highest rates of relative sea-level rise and loss. Here, the authors show that there is a strong regional component to coastal Louisiana wetland vulnerability to relative sea-level rise as well as contributing to the understanding of subsidence in the region.